2019
DOI: 10.18089/tms.2019.150203
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of experiences in boutique hotels in the context of e-WOM

Abstract: Postmodern society is characterised by consumers' hedonistic behaviours and values, in which experience consumption is a form of differentiation and social elevation. This study sought to understand consumers' online manifestations of boutique hotel experiences and individuals' motivations for engaging in electronic word-of-mouth. The research considered prior studies on experiential consumption, as well as publications focused on understanding postmodern individuals. Netnography was used to collect data on-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Boutique hotels are defined by the market in much the way supply-side research would suggest (Jones et al, 2013). Parolin and Boeing (2019) found that individuals seek differentiation in the consumption experiences of boutique hotels. Consumers expect exquisite food and beverage, distinctive layouts and interior design, and individualized service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boutique hotels are defined by the market in much the way supply-side research would suggest (Jones et al, 2013). Parolin and Boeing (2019) found that individuals seek differentiation in the consumption experiences of boutique hotels. Consumers expect exquisite food and beverage, distinctive layouts and interior design, and individualized service.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to considering size, researchers have agreed that boutique hotels should be differentiated from traditional hotels through high-quality and personalized service, individualized experiences, and unique designs and architecture (Aggett, 2007; Jones et al, 2013; McIntosh and Siggs, 2005). Parolin and Boeing (2019) argued these factors create a sense of exclusivity that boutique hotel consumers value.…”
Section: Introductionmentioning
confidence: 99%
“…Boutique hotel customers also associated boutique hotels with novel service provisions. For example, in boutique hotels in Brazil customers reported innovative services, such as dinner on an island where only one couple at a time was welcomed and the use of small treats in rooms, such as chocolates arranged in the form of the couples' initials (Parolin and Boeing, 2019). Boutique hotels in Vietnam offered customers access to spas and special treatments (Truong et al, 2020), while boutique hotels in Vietnam and Hong Kong offered customers access to transport, e.g.…”
Section: Innovative Service Provisionsmentioning
confidence: 99%
“…The emergence and rise of Information and Communication Technologies (ICTs) in the context of hospitality has provided tourists with a forum in which they can evaluate their lodgings on the internet, by reporting and evaluating establishments through User Generated Content (UGC), which generates an online reputation through electronic word-of-mouth. According to Parolin & Boeing (2019), online platforms are widely used to disseminate electronic word -of-mouth (eWOM) in various areas of tourism and hospitality. This UGC is an important aspect to be considered by managers, as managing users' comments enables them to identify failures in the service provision, providing an opportunity to optimize the company's actions and improve its performance through online reputation and increased guest satisfaction.…”
Section: Introductionmentioning
confidence: 99%